Free-radical copolymerization of 2,[3-(6-tetralino)-3-methylcyclobutyl]-2-ketoethyl methacrylate with acrylonitrile and styrene: Synthesis, characterization, and monomer reactivity ratios - Erol, Ibrahim; Ahmedzade, Misir (John Wiley & Sons Inc, 2007)
The copolymerization of the monomer 2-[3(6-tetralino)-3-methylcyclobutyl]-2-ketoethyl methacrylate with acrylonitrile and styrene was carried out in a 1,4-dioxane solution at 60 degrees C with 2,2'-azobisisobutyronitrile as an initiator. The copolymers were characterized with Fourier transform infrared, H-1-NMR, and C-13-NMR spectroscopy techniques. The thermal properties of the polymers were also studied with thermogravimetric analysis and differential scanning calorimetry. The copolymer compositions were determined with elemental analysis and H-1-NMR techniques. The monomer reactivity ratios were calculated by the application of conventional linearization methods (Fineman-Ross and Kelen-Tudos) to be less than 1 for both monomers. (c) 2007 Wiley Periodicals, Inc.
Keywords: copolymerization; radical polymerization; thermogravimetric analysis (TGA)